Assessing Employees’ Belongingness for Long-Term Sustainability of the Company: A Case of G Company, Bangkok, Thailand - Luo, Yijun; Barnes, John Arthur (ABAC ODI JOURNAL Vision. Action. Outcome, 2020)
Employees’ belongingness is related to the long-term sustainability of the company and determines the core competitive talent advantage of the company. However, many companies, especially small-medium enterprises in Bangkok, have been plagued by the weak Employees’ belongingness and high employees’ turnover. This study examined the influencing factors on Compensation&Benefits, company culture, professional training, and career development four aspects of employees’ belongingness in G company Bangkok, Thailand. The objectives of this study are first to conduct an assessment of the employee’s belongingness. Second, to propose an improvement plan to enhance employees’ belongingness for G company. This study employed a structured questionnaire comprises of 25 questions. The total actual participant respondents were 48. The researcher used descriptive statistics for demographic data and multiple regression analysis to test the relationship between Compensation&Benefits, company culture, professional training, career development, and employees’ belongingness. The finding of this paper indicated that there a positively strong relationship between Compensation&Benefits, company culture and employees’ belongingness based on the data obtained from the survey, the researcher proposed an employees’ belongingness improvement plan for G Company.